Transnational migrants, migration policies and the role of organized civil society - Díaz , Luz Marina (Sociedad y Economía, 2010)
The purpose of is article is to make a reflection about global economic crisis impacts in the most fragile population: transnational labour immigrants, and characterize the profile which is being consolidated during this process. First of all references some theoretical models how has been proposed to explain international migration labour process. Secondly, describes the main characteristics of this population and the entailment ways to global capital; them this article illustrates briefly somewhat immigration restrictive policies as economic and financial crisis effects on labour international migration flows. Finally review the international immigrants organizations reply in face to restrictive policies.